MEDIATING ROLE OF LIFE SATISFACTION IN THE RELATIONSHIP BETWEENTEACHERS' EMOTIONAL INTELLIGENCE LEVELS AND TEAMWORK - (:unkn) unknown (My University, 2020)
The aim of this study is to test the theoretical model developed for the mediating role ofteamwork in the relationship between teachers' emotional intelligence levels and lifesatisfaction. The study group of the research consists of 339 teachers, 246-women (72.6%) and93 (27.4%) men working in private and public schools in Uskudar district of Istanbul province in2018-2019 academic year. The theoretical model proposed in the research was tested with theStructural Equation Model and SPSS and AMOS were used to evaluate the data. The data of thestudy were obtained with the “Emotional Intelligence Scale”, “The Teamwork Scale” and the“Adult Life Satisfaction Scale” and Personal Information Form. The theoretical model proposedwith the collected data was tested with the Structural Equation Model. In the structural modelthat was established to test the mediating role of the teamwork variable in the relationshipbetween emotional intelligence levels and life satisfaction, it was found that the model fit indicesfit well. As a result of the analysis, the emotional intelligence levels of the teachers in therelationship established between emotional intelligence, teamwork and life satisfaction,teamwork positively and directly; it is concluded that it significantly affects their life satisfactionboth directly and indirectly. The proposed structural equation model was verified, and it wasconcluded that teamwork had a full mediating effect on the model in question. Accordingly, thehigh life satisfaction of the members of the team directly affects the job satisfaction andperformance of the individuals in the organization.

Bu araştırmanın amacı, öğretmenlerin duygusal zekâ düzeyleri ile yaşam doyumu arasındaki ilişkide, takım çalışmasının aracılık rolüne ilişkin geliştirilen teorik modelin test edilmesidir. Araştırmanın çalışma grubunu 2018-2019 eğitim öğretim yılında, İstanbul ilinin Üsküdar ilçesinde özel ve devlet okullarında çalışan 246 kadın (%72,6) ve 93 (%27,4) erkek öğretmen olmak üzere toplam 339 öğretmen oluşturmaktadır. Araştırmada önerilen teorik model Yapısal Eşitlik Modeli ile test edilmiş, verilerin değerlendirilmesinde SPSS ve AMOS kullanılmıştır. Araştırmanın verileri “Duygusal Zekâ Ölçeği”, “Takım Çalışması Ölçeği” ve “Yetişkin Yaşam Doyumu Ölçeği” ve Kişisel Bilgi Formu ile elde edilmiştir Duygusal zekâ düzeyleri ile yaşam doyumu arasındaki ilişkide, takım çalışması değişkeninin aracılık rolünü test etmek için kurulan yapısal modelde, model fit uyum indekslerinin iyi uyum verdiği tespit edilmiştir. Analizler sonucunda duygusal zekâ, takım çalışması ve yaşam doyumu arasında kurulan ilişkide öğretmenlerin duygusal zekâ düzeyleri, takım çalışmalarını olumlu yönde ve doğrudan; yaşam doyumlarını hem doğrudan hem de dolaylı olarak anlamlı bir şekilde etkilediği sonucuna ulaşılmıştır. Önerilen yapısal eşitlik modeli doğrulanmış ve takım çalışmasının söz konusu modelde tam aracılık etkisi yaptığı sonucuna ulaşılmıştır. Buna göre takımdaki üyelerin yaşam doyumlarının yüksek olması, örgütteki bireylerin iş tatminini ve performansını geliştirebilir.
ÖĞRETMENLERİN DUYGUSAL ZEKÂ DÜZEYLERİ İLE YAŞAM DOYUMU ARASINDAKİ İLİŞKİDE TAKIM ÇALIŞMASININ ARACILIK ROLÜ